The effect of knowledge sharing on ambidextrous innovation: Triadic intellectual capital as a mediator - Zhenyang Zhang; Xinyuan Wang; Dongphil Chun (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
There is no doubt that the primary reason that firms encourage knowledge sharing is to drive innovation. As nutrients for innovation, what role do the different elements of intellectual capital play in this relationship? When we consider the ambidexterity of enterprise innovation - exploratory and exploitative - how do the different elements of intellectual capital affect the relationship between them? This study adopts a triadic perspective to divide intellectual capital into human, structural and relational capital. We analyzed 349 questionnaires from high-tech enterprises and found that knowledge sharing had a significantly positive effect on all three elements of intellectual capital, and human capital and structural capital had a positive effect on ambidextrous innovation. Relational capital had a positive effect on exploitative innovation but no significant effect on exploratory innovation. Unexpectedly, there was no direct effect of knowledge sharing on ambidextrous innovation, and the elements of intellectual capital play full mediations among them. This may suggest that firms should pay more attention to the role of relational capital when they adopt exploitative innovation. At the same time, we remind managers that innovation may be promoted only when knowledge sharing increases intellectual capital. Therefore, the misuse of management tools should be avoided, and ineffective management practices should be reduced. In addition, we explored the relationship between knowledge sharing and the open innovation paradigm and made some suggestions for future research.
Keywords: 650; open innovation; ambidextrous innovation; exploitative innovation; exploratory innovation; knowledge sharing; triadic intellectual capital